Pediatric Physical Assessment. (Academic Video Online, 2013)
An essential part of preventive pediatric medicine is a complete and thorough physical assessment. Pediatric Physical Assessment Part 2 covers the examination of internal body functions, including the chest and lungs, heart, abdomen, musculoskeletal system and neurological system. The course presents a systematic, step-by step process for performing a complete internal physical exam on a preschool-age child.